A novel parallel texture feature extraction method using log-gabor filter and singular value decomposition (SVD) - Ratul, Md Aminur Rab; Raja, Sharif Ahmmad; Uddin, Jia (© 2017 ACM, 2018)
This conference paper was published in the ACM International Conference Proceeding Series [© 2017 ACM] and the definite version is available at : http://doi.org/10.1145/3036331.3036352 The Journal's website is at: https://dl.acm.org/citation.cfm?doid=3036331.3036352